2022
DOI: 10.1108/er-01-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Integrating green human resource management and circular economy to enhance sustainable performance: an empirical study from the Qatari service sector

Abstract: PurposeThis study aims to contribute to the current Green human resource management (HRM) field by providing an empirical examination of a comprehensive model that tests the effect of green strategic intent on Green HRM implementation, the possible effect of Green HRM and green empowerment on circular economy, and the effect of circular economy on sustainable performance. It examines the mediating effect of circular economy on the link between Green HRM and sustainable performance.Design/methodology/approachTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 126 publications
4
45
0
Order By: Relevance
“…Many petrochemical companies like MOPCO Egypt for manufacturing fertilisers is keen from the beginning and before establishing their factories to evaluate the environmental impact depending on the largest consulting companies specialised in this field. This emphasizes the need to leverage green practices to a higher level by adopting a comprehensive environmental management system including GIC to enable organizations to achieve sustainable performance at the corporate level (Obeidat et al, 2022) Results Showed that firms tend to adopt GI to a greater extent when they have higher GIC. Specifically, GHC and GSC have a significantly positive effect on GI due to their direct contribution in supporting GI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many petrochemical companies like MOPCO Egypt for manufacturing fertilisers is keen from the beginning and before establishing their factories to evaluate the environmental impact depending on the largest consulting companies specialised in this field. This emphasizes the need to leverage green practices to a higher level by adopting a comprehensive environmental management system including GIC to enable organizations to achieve sustainable performance at the corporate level (Obeidat et al, 2022) Results Showed that firms tend to adopt GI to a greater extent when they have higher GIC. Specifically, GHC and GSC have a significantly positive effect on GI due to their direct contribution in supporting GI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GRC has a direct impact on GI. Therefore, the firm can gain a competitive advantage over its competitors and then attain BS if it considers and protects the interest of its stakeholders, considers environmental issues, and manages its intellectual capital efficiently (Obeidat et al, 2022;Sabbir and Taufique, 2021;Chaudhry et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Figge et al (2021) reported that the transformation of resources into circular resources contributes toward more circularity (Figge et al, 2021). A study conducted by Obeidat et al (2022) reported about the possible impact of green human resource management (HRM) on the execution of CE. Results suggested that CE and green HRM have interconnected patterns.…”
Section: Existing Work On Circular Economymentioning
confidence: 99%
“…This includes practices such as recruitment and selection, training and development, and even compensation that are centred on green strategies. The research by Obeidat et al . (2023) seeks to investigate how Green HRM works to impact the development of a circular economy within an organisation.…”
Section: Using All Means Availablementioning
confidence: 99%